Development of Website-Based Instructional Media on Complex English Grammar for Tenth-Grade Students at SMAN 1 Batukliang Utara, Central Lombok - Masyudi, Masyudi; Hadi, M. Wahyu; Muliadi, Mul (JURNAL ASIMILASI PENDIDIKAN, 2025)
The integration of technology into education has become increasingly essential, especially in enhancing students' mastery of abstract language concepts such as complex grammar. Despite numerous digital tools available, many high school classrooms still rely on conventional methods, resulting in low student motivation and poor grammar comprehension. This study aims to develop and evaluate a website-based instructional media using Canva to improve students’ understanding of complex English grammar. Employing a Research and Development (R&D) design with the ADDIE model, the study involved media validation by experts and a quasi-experimental test with a pretest-posttest control group design. The developed media was assessed for feasibility by media, material, and language experts and scored an average of 82.6%, categorized as highly feasible. Additionally, the experimental group that used the Canva-based media achieved a significant improvement in their grammar scores, with an N-Gain score of 0.64 (moderate–high category), compared to the control group’s 0.26 (low category). The findings indicate that website-based media is effective in improving grammar achievement, enhancing student motivation, and fostering autonomous learning. The study concludes that Canva is a practical and scalable tool for supporting complex grammar instruction in high school settings, and its implementation should be encouraged for broader adoption in digital learning environments.